1985
DOI: 10.1111/j.1469-8749.1985.tb14136.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Gross Motor Development: The Influences of Race, Sex and Socio‐economic Status

Abstract: SUMMARY The ages at attainment of 12 gross motor milestones were obtained prospectively during well‐baby visits in the first two years of life for 381 children. All had been born at term and were judged to be normal at one year. A longitudinal analysis, using an index summarising each chilďs progress for eight selected milestones, is reported for the 284 children for whom data were complete. A high percentage of parents were able to report the age at attaining milestones with an acceptable degree of variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
6

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 6 publications
3
54
0
6
Order By: Relevance
“…A previous study on white and black infants showed that the age that these milestones were achieved differed by sex and ethnic group, but that all infants rolled from prone-to-supine before supine-to-prone i.e. the reverse of our data (see Table II; Capute et al 1985). In contrast to these studies, Piper and Darrah (1994) note that 50% of infants roll prone-to-supine without and with trunk rotation at 6 and 7 months respectively and 50% roll supine-to-prone without and with trunk rotation at about 5.6 months and 6.6 months respectively.…”
Section: Discussionmentioning
confidence: 29%
See 1 more Smart Citation
“…A previous study on white and black infants showed that the age that these milestones were achieved differed by sex and ethnic group, but that all infants rolled from prone-to-supine before supine-to-prone i.e. the reverse of our data (see Table II; Capute et al 1985). In contrast to these studies, Piper and Darrah (1994) note that 50% of infants roll prone-to-supine without and with trunk rotation at 6 and 7 months respectively and 50% roll supine-to-prone without and with trunk rotation at about 5.6 months and 6.6 months respectively.…”
Section: Discussionmentioning
confidence: 29%
“…Illingworth (1979) noted that the normal child rolls prone-to-supine at about 24 weeks (5.6mo) and from supine-to-prone at 28 weeks (6.5mo), and states that this information is based on his own experience and work by Arnold Gesell. However subsequent clinical experience indicated that infants were showing more rapid motor development than would be expected from these traditional studies (Capute et al 1985). The Denver Developmental Screening Test, revised and restandardized in 1992, was based on 2096 black, Hispanic, and white infants in Colorado, USA and differs somewhat to the previous version (Table III; Frankenburg et al 1981Frankenburg et al , 1992.…”
Section: Discussionmentioning
confidence: 99%
“…He found that boys appeared to walk or sit earlier than girls, whereas girls developed functional skills such as vocalising and grasping sooner. Others have also identified sex differences in motor performance in infants and children; boys usually better at locomotor skills and girls better at balancing skills and flexibility tasks (e.g., Anastasi 1981;Capute et al 1985;Hands and Larkin 1997;Pedersen et al 2003;Piek et al 2002;Thomas and French 1985;Van Waelvelde et al 2003).…”
Section: Sex Differences In Motor Abilitymentioning
confidence: 99%
“…Many of these tools were developed last century but only the more popular tests that have been developed or updated in the last 20 years will be described here. It is essential that the norms for these assessment tools are regularly updated as there is evidence for a trend of earlier onset of common motor milestones more recently compared with earlier in the last century (e.g., Capute et al 1985;Gallahue and Ozmun 2002;Piek 2006). There are many factors that could contribute to this, although changes in child-rearing practices may be a major factor given that research has identified cultural differences in child-rearing resulting in different rates of motor milestone development (e.g., Hamilton 1981;Super 1976).…”
Section: Motor Assessment Testsmentioning
confidence: 99%
“…Such knowledge could facilitate the differentiation between preterm newborns with actual motor deficits and those whose pace of acquisition is slower, but does not lead to future motor impairment. Investigations 8,22,23 on normal infants in order to determine the profile of motor skill acquisition, regarding both pattern and pace of development, reported differences in the pattern of motor development between children from different countries. These differences occurred in children belonging to different cultural groups and also within the same cultural group, confirming that the neuropsychomotor development (NPMD) depends on biological, cultural and environmental risk factors.…”
Section: Discussionmentioning
confidence: 99%